Novel Technique to Reduce the Incidence of SSI after Colorectal Surgery. Issue 7 (July 2019) - Kay, Danielle; Bhakta, Avinash; Patel, Jitesh A.; Hourigan, Jon S.; Kumar, Shyanie; Davenport, Daniel; Beck, Sandra J.
SSI is a leading cause of morbidity and increases health-care cost after colorectal operations. It is a key hospital-level patient safety indicator. Previous literature has identified perioperative risk factors associated with SSI and interventions to decrease rate of infection. The purpose of this study was to evaluate the impact of blowhole closure on the rate of superficial and deep SSI. The ACS-NSQIP database was queried for patients undergoing colectomy at the University of Kentucky from 2013 to 2016. Retrospective chart review was performed to gather demographic data and perioperative variables. Wounds left open and packed were excluded. Rates of postoperative SSI were measured between the groups. One thousand eighty-three patients undergoing elective and emergent colectomy were reviewed. Nine hundred and forty-five had closed incision and 138 had blowhole closure. Patient characteristics between the groups were well matched. Patients with a blowhole closure were more likely to have an open procedure ( P = 0.037) and a higher wound class ( P < 0.001). The rate of superficial and deep SSI was 9.1 per cent in patients with a closed incision and 5.1 per cent in patients with blowhole closure ( P = 0.142). With adjustment for approach and wound class, blowhole closure decreased the incidence of SSI ( P = 0.04). There was no significant difference in morbidity or mortality. Patients undergoing elective and emergent colectomy had decreased incidence of SSI when blowhole closure was used. Given that it does not increase resource usage and its technical ease, blowhole closure should become the standard method of surgical wound closure.